2011
DOI: 10.14393/rbcv62n1-43668
|View full text |Cite
|
Sign up to set email alerts
|

Módulos Em Matlab Para Interpolação Espacial Pelo Método De Krigagem Ordinária E Do Inverso Da Distância

Abstract: Este trabalho tem como objetivo apresentar um conjunto de módulos desenvolvidas em MATLAB para interpolação de dados espaciais por meio da krigagem ordinária e do inverso da distância elevada a uma potência. Os dados de entrada são vetores da posição das amostras (x, y) e seus respectivos atributos (z). É considerada dependência espacial do atributo do tipo isotrópica. Os módulos construídos para krigagem ordinária calculam as semivariâncias experimentais, os parâmetros dos modelos teóricos (esférico, gaussian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
1
0
2
Order By: Relevance
“…So, the closer it is, the more it contributes. This method was employed here with the power of two, but even though the use of different values could potentially impact the results, other researchers have demonstrated that varying these values has a low impact on the outcomes (Rahman et al, 2023;Xavier et al, 2010). These two methods ended up hindered in this study case due to the non-uniformity of the data (Figure 5) and higher correlations were not found for closer station (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…So, the closer it is, the more it contributes. This method was employed here with the power of two, but even though the use of different values could potentially impact the results, other researchers have demonstrated that varying these values has a low impact on the outcomes (Rahman et al, 2023;Xavier et al, 2010). These two methods ended up hindered in this study case due to the non-uniformity of the data (Figure 5) and higher correlations were not found for closer station (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…O procedimento de ajuste não deve ser direto e/ou automático, mas sim interativo, pois neste processo o analista deve verificar a adequação do modelo ao semivariograma experimental. Caso seja necessário, o ajuste deve ser refeito (CAMARGO, 1998), sendo os modelos esférico, exponencial e gaussiano, os mais comumente utilizados (XAVIER, 2010).…”
Section: Introductionunclassified
“…Contudo, os modelos mais utilizados nas análises de dados das ciências agrárias são os modelos esférico, exponencial e gaussiano (Figura 2) (VIEIRA, 2000;XAVIER, 2010).…”
Section: Modelos De Semivariogramasunclassified